A CFD Study with Fuzzy Logic Pitch Angle Turbine Control Implementation for OWC Generation System - Mansour Madaci; Djallel Kerdoun (Institute of Advanced Engineering and Science, 2017)
The paper takes the improvement of the performance for an OWC converter from the mechanical side. A FEM model of the OWC conversion structure was proposed, studied and simulated using a CFD simulator. A novel wave generation method was applied through the RWMD method (Real Wave Model Simulator) instead of using an ordinary sin wave generator on the tank to make the waves the closest possible to the real sea waves. A mechanical prototype was built for this purpose to get an oscillated wave model. On the electrical side, a pitch angle control system based on fuzzy set was applied on the turbine to be auto-adapted for the fast variation of the airflow speed to establish and maximize the extracted power from the OWC device. The model have been studied, simulated, implemented and tested to validate the obtained results.